2012
DOI: 10.3758/s13420-012-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Associative foundation of causal learning in rats

Abstract: Are humans unique in their ability to interpret exogenous events as causes? We addressed this question by observing the behavior of rats for indications of causal learning. Within an operant motor-sensory preconditioning paradigm, associative surgical techniques revealed that rats attempted to control an outcome (i.e., a potential effect) by manipulating a potential exogenous cause (i.e., an intervention). Rats were able to generate an innocuous auditory stimulus. This stimulus was then paired with an aversive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Although by no means a new question, the publication of Blaisdell et al's controversial article in Science (2006) on causal reasoning in rats prompted widespread proliferation of research on related questions, growing substantially from virtually 0% in the first 5 year period to roughly 10% in the most recent 5 years (see Figure 2b). The general question here is whether dissociable mechanisms exist for implicit conditioning and explicit causal or propositional reasoning, and how widespread the latter is across species (Dwyer, Starns, & Honey, 2009;Polack, McConnell, & Miller, 2013;Simms, McCormack, & Beckers, 2012). One central issue is whether apparent causal reasoning, in humans or in nonhuman animals, can be parsimoniously explained using simple associative models such as the Pearce (Pearce, 2002) or Rescorla-Wagner (Rescorla & Wagner, 1972) models of learning (Dwyer et al, 2009;Polack et al, 2013;Simms et al, 2012).…”
Section: Causal Reasoningmentioning
confidence: 99%
“…Although by no means a new question, the publication of Blaisdell et al's controversial article in Science (2006) on causal reasoning in rats prompted widespread proliferation of research on related questions, growing substantially from virtually 0% in the first 5 year period to roughly 10% in the most recent 5 years (see Figure 2b). The general question here is whether dissociable mechanisms exist for implicit conditioning and explicit causal or propositional reasoning, and how widespread the latter is across species (Dwyer, Starns, & Honey, 2009;Polack, McConnell, & Miller, 2013;Simms, McCormack, & Beckers, 2012). One central issue is whether apparent causal reasoning, in humans or in nonhuman animals, can be parsimoniously explained using simple associative models such as the Pearce (Pearce, 2002) or Rescorla-Wagner (Rescorla & Wagner, 1972) models of learning (Dwyer et al, 2009;Polack et al, 2013;Simms et al, 2012).…”
Section: Causal Reasoningmentioning
confidence: 99%
“…But when nonhumans make similarly optimal choices, many researchers are inclined to talk about the underlying ‘automatic’ behavioral principles at work without appealing to any sort of conscious reasoning as is implied by rationality . The tendency for researchers to provide different accounts of similarly adaptive or maladaptive behaviors seen in humans and nonhumans is likely fueled by our introspecting about our own behaviors (see Polack, McConnell, & Miller, 2013, for a discussion of this issue with respect causal reasoning). Here we will regard so-called conscious reasoning as either (a) an emergent property of underlying behavioral principles (i.e., a different level of analysis rather than an alternative account), or (b) basically epiphenomenal with respect to behavioral choice.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Other studies with rats pressing levers have been phrased in terms of intervention, but there is variety to how intervention has been conceptualized, and to its assumed significance to learning. For instance, Polack, McConnell, and Miller (2013) "assumed that changes in operant responding consistent with the subject's motivation reflected goal-directed behavior, which [they] equated with intervention, and therefore constituted behavior indicative of causal knowledge" (p. 27-28). This approach has had a very influential precedent in the thinking of Shanks and Dickinson (e.g., 1991;Dickinson, 2001).…”
mentioning
confidence: 99%
“…This approach has had a very influential precedent in the thinking of Shanks and Dickinson (e.g., 1991;Dickinson, 2001). Polack et al (2013) showed that instrumental responding tracks outcome devaluation (e.g., Adams & Dickinson, 1981) with an aversive stimulus. However, granting their assumption circumvents the questions about intervention the present study attempts to address.…”
mentioning
confidence: 99%